A Retrospective Clinical Investigation of the Safety and Adverse Effects of Pantoprazole in Hospitalized Ruminants - Smith, Joseph S.; Kosusnik, Austin R.; Mochel, Jonathan P. (Frontiers in Veterinary Science, 2020)
Clinical safety data for the use of gastroprotectants in hospitalized ruminants is lacking. In human patients, multiple adverse effects are possible from the use of pantoprazole including hematologic and electrolyte abnormalities as well as anaphylaxis and edema. The medical records of all hospitalized cattle, goats and sheep administered pantoprazole over an approximately 5 year period were retrospectively analyzed for adverse effects. Seventy-nine eligible patients were observed. Hypomagnesemia was observed post pantoprazole administration in ten cattle; however, no significant changes were noted when compared to baseline before pantoprazole administration. Significant changes were noted in serum indicators of hepatic and renal function, however, these represented downwards trends that were most likely clinically insignificant. Anaphylaxis post-pantoprazole administration was not observed, however seven cattle displayed edema after pantoprazole administration. Veterinary clinicians should be aware of the potential for hypomagnesemia in hospitalized ruminants being administered pantoprazole and monitor patients accordingly. While these preliminary retrospective results indicate that pantoprazole may be a safe adjunctive therapy in hospitalized ruminants, additional studies are necessary to further determine the safety and toxicity of pantoprazole in ruminants.